(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The improvement of information technologies in the education system involves refining the content, organizational forms, methods, and means of teaching to enhance the practical skills of future specialists and workers in the rapidly changing information environment. The article discusses the relevance of organizing computer science education at the present stage of forming an information society and presents effective tools and methods for their implementation.